Perceptions Toward Leisure Activities and Prolonged Sitting Among Saudi Adults – A Cross-sectional Community-Based Study - Samarkandi, Osama A. (Asian Journal of Pharmaceutics (AJP), 2024)
Background and Objective: Leisure activities encompass a wide range of recreational pursuits that individuals engage in during their free time. This study aims to assess the perceptions toward leisure activities and prolonged sitting among Saudi adults in Riyadh, Saudi Arabia. Materials and Methods: A cross-sectional community-based study was conducted among people living in Saudi Arabia to assess the perception of adults toward leisure activities and prolonged sitting using a total of 25-item questionnaires divided into four sections on the 5-point Likert scale. Results: Two hundred and one (n = 201) Saudi adults completed the survey. In this study, 51.2% of the males were participated. With regard to time spent on leisure activities, such as social media, 28.4% of the respondents spent 30 min, followed by coffee and dessert by 70.6% for 2 h, related activity by 63.2% for >4 h, business-related activity by 30% for <30 min, family time by 30% for 2 h, and 29.4% spend <30 min watching television. Furthermore, 59.2% of participants believed that sitting for long periods of time was harmful to their health. Conclusion: Leisure activities and prolonged sitting have emerged as important topics concerning the health and well-being of Saudi adults. The high prevalence of sitting time and its associated health risks necessitate the implementation of strategies to reduce prolonged sitting and increase physical activity levels. By promoting leisure activities and creating a supportive environment, Saudi adults can be encouraged to adopt a more active lifestyle, leading to improved overall health and well-being.